Pertanggungjawaban Pidana Terhadap Pelaku Pada Kegiatan Bantuan Sosial Covid 19 - Darson Lokbere; A. A. Sagung Laksmi Dewi; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2021)
The coronavirus-19 outbreak that has rapidly infected humans and spread globally has become a health issue that breeds concern and chaos. In everyday life today there are many injustices that are continuously present in society. The lack of compliance with the law, weak knowledge of the community, and individualistic behavior and stupid times in society make the owners of power arbitrary towards its people. Problem formulation (1) What is the arrangement for the implementation of bansos COVID 19? (2) How is criminal liability for the perpetrators of the implementation of bansos COVID 19? To address the impact of the Covid-19 pandemic, the government issued various policies that allow government officials to make extraordinary measures in emergencies, but did not rule out the possibility that ownership of such authority would pose a great risk to governments and state officials and to the emergence of stowaways who take advantage of this pandemic situation.